Severe obstructive sleep apnea after concurrent chemoradiotherapy for laryngeal and hypopharyngeal cancer managed by CPAP. Issue 6 (December 2022) - Inoshita, Ayako; Matsumoto, Fumihiko; Ohba, Shinichi; Sata, Naoko; Matsuoka, Rina; Suzuki, Yo; Ito, Shin; Koiwai, Hiroko; Shiroshita, Nanako; Kasai, Takatoshi; Ikeda, Katsuhisa
Abstract: Concurrent chemoradiotherapy (CCRT) is one of the most promising treatments for advanced head and neck cancer (HNC). On the other hand, CCRT may induce severe edema in laryngo-pharyngeal structures in association with radiation. This is a report of a 66-year-old man with severe obstructive sleep apnea (OSA) associated with edema in laryngo-hypopharynx after CCRT for advanced laryngeal and hypopharyngeal cancer. Tracheostomy was avoided and OSA was controlled by continuous positive airway pressure (CPAP). Subjective symptoms of sleepiness were improved. Though laryngeal edema appeared during the course of CCRT in this case, OSA was not evaluated until snoring had been pointed out and he complained of sleepiness. CCRT for laryngeal and hypopharyngeal cancer have a risk of occurrence of OSA due to irreversible mucous edema in the upper airway. Patients for whom CCRT is planned should be informed about the occurrence of OSA before the treatment because symptoms associated with OSA can negatively impact not only the daytime quality of life but also increase the risk of cardiovascular events. The OSA treatment for post CCRT would be expected to have a positive impact on not only cardiovascular and metabolic systems but also on the cancer treatment survival rate.